2020
DOI: 10.15585/mmwr.mm6939a6
|View full text |Cite
|
Sign up to set email alerts
|

Deaths and Years of Potential Life Lost From Excessive Alcohol Use — United States, 2011–2015

Abstract: Excessive alcohol use is a leading cause of preventable death in the United States (1) and costs associated with it, such as those from losses in workplace productivity, health care expenditures, and criminal justice, were $249 billion in 2010 (2). CDC used the Alcohol-Related Disease Impact (ARDI) application* to estimate national and state average annual alcohol-attributable deaths and years of potential life lost (YPLL) during 2011-2015, including deaths from one's own excessive drinking (e.g., liver diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 9 publications
1
61
0
Order By: Relevance
“…impaired driving (National Center for Statistics & Analysis, 2020).The Centers for Disease Control and Prevention produced a report using acute exposure to alcohol and found that between 2011 and 2105, the alcohol-attributable fraction among men ranged from 0.15 (among those aged 65+) to 0.49 (those aged 25-34), and among women between 0.11 (among those aged 65+) and 0.40 (those aged 20-34) (Centers for DiseaseControl & Prevention., 2019;Esser et al, 2020). In contrast, our estimated PAR of alcohol for road injuries in the United States in 2019 was 10.16%, suggesting again a possible underestimation of PAR by the GBD, possibly due to the GBD study's reliance on chronic alcohol consumption data.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…impaired driving (National Center for Statistics & Analysis, 2020).The Centers for Disease Control and Prevention produced a report using acute exposure to alcohol and found that between 2011 and 2105, the alcohol-attributable fraction among men ranged from 0.15 (among those aged 65+) to 0.49 (those aged 25-34), and among women between 0.11 (among those aged 65+) and 0.40 (those aged 20-34) (Centers for DiseaseControl & Prevention., 2019;Esser et al, 2020). In contrast, our estimated PAR of alcohol for road injuries in the United States in 2019 was 10.16%, suggesting again a possible underestimation of PAR by the GBD, possibly due to the GBD study's reliance on chronic alcohol consumption data.…”
mentioning
confidence: 62%
“…Limitations of the GBD data are related to the quality and validity of alcohol consumption measurement across countries (recorded and unrecorded per capita alcohol consumption), and reduced availability of data for different consumption patterns in age and sex groups, and for periods further away in time (GBD 2016Alcohol Collaborators, 2018. With only a few high-income countries, such as the USA, having the resources to produce their own burden of disease estimates for alcohol use (Esser et al, 2020), currently there are only 2 sources that aggregate global mortality data by injury (including road injuries) and associated risk factors (including alcohol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding author: Michele K. Bohm, mbohm@cdc.gov, 770-488-3928. 1 Division of Population Health, National Center for Chronic Disease Prevention and Health Promotion, CDC; 2 Division of HIV Prevention, National Center for HIV, Viral Hepatitis, STD, and TB Prevention, CDC.…”
mentioning
confidence: 99%
“…B etween 2011 and 2015, excessive drinking was responsible for an average of 93,296 deaths (255 per day) and 2.7 million years of potential life lost (29 years lost per death, on average) each year in the United States. 1 Within this estimate, which comprised deaths directly caused by alcohol, deaths partially attributable to alcohol, and deaths due to someone else's drinking, alcoholassociated liver disease (ALD) was the leading chronic cause of directly alcohol-attributable deaths overall (n ¼ 18,164) and among males (n ¼ 12,887) and females (n ¼ 5,277). Based on estimates of sales of alcoholic beverages and recent studies indicating that alcohol consumption increased subsequent to April 2020, these trends have been exacerbated during the COVID-19 pandemic.…”
mentioning
confidence: 99%